Super-resolution optical microscopy resolves network morphology of smart colloidal microgels. Issue 7 (2nd February 2018) - Bergmann, Stephan; Wrede, Oliver; Huser, Thomas; Hellweg, Thomas
Abstract : We present a new method to resolve the network morphology of colloidal particles in an aqueous environment via super-resolution microscopy. The 3D structure of thermoresponsive microgels with different cross-linker content is resolved and compared to established models. Abstract : We present a new method to resolve the network morphology of colloidal particles in an aqueous environment via super-resolution microscopy. By localization of freely diffusing fluorophores inside the particle network we can resolve the three dimensional structure of one species of colloidal particles (thermoresponsive microgels) without altering their chemical composition through copolymerization with fluorescent monomers. Our approach utilizes the interaction of the fluorescent dye rhodamine 6G with the polymer network to achieve an indirect labeling. We calculate the 3D structure from the 2D images and compare the structure to previously published models for the microgel morphology, e.g. the fuzzy sphere model. To describe the differences in the data an extension of this model is suggested. Our method enables the tailor-made fabrication of colloidal particles which are used in various applications, such as paints or cosmetics, and are promising candidates for drug delivery, smart surface coatings, and nanocatalysis. With the precise knowledge of the particle morphology an understanding of the underlying structure–property relationships for various colloidal systems is possible.